SMART SEIRS - Hassim, Hasniza; Mohd Helmi, Mohd Firdaus; Mohamed Sawal, Mohd Zool Hilmie; Mohamad Tanuri, Zati Atiqah; Arif, Zuraidah (Universiti Teknologi MARA, Kedah, 2022)
Students with learning disabilities have difficulties in specific areas of academic achievement due to impairment in one or more of the cognitive processes related to learning. One of the defining features of a specific learning disability is that the difficulty continues to exist, despite appropriate instruction and intervention. SMART SEIRS is intended to improve the students with learning disabilities in information retrieval skills. It also promotes a better academic life by enriching continuous lifelong learning. The potential of SMART SEIRS may contribute to increase information handling skills among students with learning disabilities in Malaysia, as it has been developed due to consultation service provided by the researchers at Sekolah Menengah Pendidikan Khas Vokasional Merbok, Kedah, for the project of Digital Learning Applications for students with special educational needs (specific for information retrieval system).